Qualidade de vida em mães de crianças sorointerrogativas ao HIV/AIDS - Lima, Flávio Lúcio Almeida (2009)
In the AIDS context, the vertical transmission of the HIV arises as a serious problem which surveillance, control and prevention are epidemiologically necessary. The antiretroviral therapy represents a great conquest in this direction, with beginning in the prenatal, intervention in the childbirth and accompaniment until the second year of children s life. This situation of undefined diagnostic of seropositivity for HIV/AIDS becomes these children in serointerrogative in respect to the HIV. In this sense, become important to verify how AIDS exercises influence in the quality of life of involved ones, mainly when proved it the expectation of a child s seropositive diagnosis. Objective: To analyze the quality of life in mothers of serointerrogative children to the HIV. Method: The sample was constituted by 49 mothers (pregnant or non-pregnant) of serointerrogative for HIV children. Used it the following instruments: 1) Brief version of World Health Organization Quality of Life (WHOQOL-brief); 2) Subjective Well Being Scale (SWBS), specifically, the second part of scale that concerns to life satisfaction; 3) In-depth interview; and 4) Socio-demographic questionnaire. Results: Life satisfaction: The studied mothers had presented a good index of life satisfaction (M= 64,7; SD= 8,05). It was perceived a statistically significant difference between life satisfaction and the number of children (p= 0,03). The mothers with three or more children (M= 67,7; SD= 6,04) had presented a bigger life satisfaction in relation to those with one or two children (M= 62,9; SD= 8,6). Quality of life (QV): The most of the participants evaluated the quality of life and health satisfaction in a positive way. In the general evaluation, 53.1% of the participants had chosen as good or very good their quality of life, and 49.9% had affirmed to be satisfied or very satisfied with their health. With concerns to health satisfaction was perceived a significant difference (p= 0,001) to the educational degree. The participants with lesser educational degree had presented themselves more satisfied with their health (M= 71,67; SD= 21,58) than those with bigger educational degree. In specific domains, the quality of life was higher to the Physical (M= 63,3; SD= 15,7) and Social (M= 61,9; SD= 26,4), and minors in the Psychological (M= 54,9; SD= 14,9) and Environmental (M= 44,8; SD= 14,8). Was observed a statistically significant variance between the physical (p= 0,02) and environmental (p= 0,005) domains. The participants with familiar income above of a minimum wage revealed themselves with a bigger quality of life in the physical (M= 73,2; SD= 6,2) and environmental (M= 64,1; SD= 15,8) domains. It was perceived statistically significant difference between the civil state and the psychological domain (p= 0,04). The mothers who affirmed to have a steady union had presented a higher quality of life in the psychological domain (M=57,6; SD=15,4). Interview: In speech analyses, emerged two thematic axes, as following: 1) Coexistence with HIV/AIDS - composed by the categories diagnosis, AIDS perception, support, coping and treatment adherence; and 2) Seropositive motherhood with the following categories: positive feelings, feeling of guilty and expectation of diagnosis. Conclusion: Despite to the motherhood of serointerrogative child experience, the most studied mothers presented a positive quality of life. The presented results confirm the necessity of study the current approaches of the coexistence with HIV/AIDS. In this sense, the discussion of coping, adjustment and quality of life of people that coexists with HIV/AIDS is a necessary debate to increase the comprehension of the AIDS effects.